Coagulation inhibitors and activated protein C resistance in recurrent pregnancy losses in Indian women - P Lalita Jyotsna; Sunita Sharma; Shubha S Trivedi (Wolters Kluwer Medknow Publications, 2011)
Background: Thrombophilias, both acquired and inherited, have been investigated in the etiopathogenesis of unexplained recurrent pregnancy loss. Aim: To study coagulation inhibitors and activated protein C resistance (APCR) in recurrent pregnancy losses (RPL) occurring in second and third trimesters. Materials and Methods: A total of 30 pregnant women (group A) with two or more recurrent unexplained fetal loses were evaluated for APCR, protein C deficiency, protein S deficiency, antithrombin deficiency, and antiphospholipid antibodies (APLA). Thirty age-matched controls were taken (group B) comprising of pregnant women with at least one live issue. Statistical Analysis: Comparisons between two group frequencies and group means were made using Chi square test and Student's t test, respectively. Results: Protein C and protein S levels were reduced in group A compared with group B and the difference was statistically significant (P=0.005 and P=0.032, respectively). The mean value of antithrombin was slightly reduced in group A compared with group B. APCR was observed in 16.6% cases and 3.3% controls. However, the difference was not statistically significant. APLA was observed in 20% cases and none of the controls. Of these, lupus anticoagulant was positive in 16.6% cases and anticardiolipin antibodies in 10% cases. Combined defects were seen in seven patients. Conclusion: There is a significant risk of RPL in pregnant women with thrombophilias. Therefore, screening for thrombophilias may be justified in pregnant women with unexplained recurrent fetal wastage, especially in second and third trimester.